2020
DOI: 10.1111/and.13667
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Alpha‐Linolenic acid on Lipopolysaccharide‐Induced Orchitis in mice

Abstract: Polyunsaturated fatty acids (PUFAs) consist of alpha-linolenic acid (ALA) (18:3, n-3) and linoleic acid (LA) (18:2, n-6) (Erdinest, Shmueli, Grossman, Ovadia, & Solomon, 2012). PUFAs are essential forms of fatty acids; thus, they cannot be produced by the human body and must be obtained as nutrients in the diet (Besler, 2006). ALA is a key molecule required for synthesis of arachidonic acid; it also serves as a precursor molecule for the formation of eiocosapentanoic acid (EPA) and docosahexaenoic acid (DHA) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…47 Furthermore, ALA can inhibit the translocation of NF-κB and the phosphorylation of MAPK, and finally reduced the expression of inflammatory factors such as cyclooxygenase-2 (COX-2) and TNF-α. 48 These results are also similar to the finding in the present research that ALA as the main component can inhibit the inflammatory cytokine (IL-6 and TNF-α) release in the inflammation cell model.…”
Section: Discussionsupporting
confidence: 92%
“…47 Furthermore, ALA can inhibit the translocation of NF-κB and the phosphorylation of MAPK, and finally reduced the expression of inflammatory factors such as cyclooxygenase-2 (COX-2) and TNF-α. 48 These results are also similar to the finding in the present research that ALA as the main component can inhibit the inflammatory cytokine (IL-6 and TNF-α) release in the inflammation cell model.…”
Section: Discussionsupporting
confidence: 92%
“…For the DSS‐induced ulcerative colitis mice, ALA (30–60 mg/kg) also reduced the expression of IL‐6, COX‐2, TNF‐α, and M1‐positive macrophages (J. Kim et al, 2020; Reifen, Karlinsky, Stark, Berkovich, & Nyska, 2015). Also, ALA (10–200 mg/kg) improved LPS‐induced orchitis and cystitis in mice through the reduced expression of IL‐6, TNF‐α, COX‐2, PLA 2 , and iNOS by inhibiting the activation of the NF‐κB signaling pathway (Kapl, Ok, & Demir, 2017; Ok, Kaplan, Kizilgok, & Demir, 2020). ALA (360–1800 mg/kg) improved lung injury in LPS‐induced mice by reducing the infiltration of total cells and neutrophils, increasing the number of macrophages, and inhibiting the expression of TNF‐α, IL‐6, and IL‐1β (Zhu et al, 2020).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…Likewise, linolenic acid (V83) was assumed to be transformed into methyl linolenate (V82) by esterification reaction during stir-frying [ 38 ]. Previous study has reported that linolenic acid shows bioactivities such as anti-inflammatory and antioxidant effects [ 40 ]. Therefore, it might be also related to the disappearance or significant decrease of linolenic acid ( Table 2 ) and efficacy changing under the stir-fry processing of SS.…”
Section: Resultsmentioning
confidence: 99%